PENGARUH COMPUTER ANXIETY DAN COMPUTER ATTITUDE TERHADAP KEAHLIAN BERKOMPUTER MAHASISWA AKUNTANSI - Setyawan, Ridho Ilham; lah, Syaeful (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to examine the influence of computer anxiety (computer fear and computer anticipation) and computer attitude (computer pessimism and computer optimism) towards the computer self-efficacy of accounting students. This research was conducted at the Brawijaya University School of Economics and Bussiness. This study received 86 responses. The research used regression techniques to test the research data with SPSS software. Result of analysis for this model show that simultaneously, the computer fear, computer anticipation, computer pessimism and computer optimism effects the computer self-efficacy. Partial test result showed that computer fear and computer anticipation affects the computer self-efficacy, while computer pessimism and computer optimism does not affect the computer self-efficacy of accounting students. The implication of this research is relevant to the faculty to consider the factor that influence the computer self-efficacy.Keywords: computer self-efficacy, computer fear, computer anticipation, computer pessimism, computer optimism.